2017
DOI: 10.1093/ecco-jcc/jjx153
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Faecal Microbiota in Paediatric Crohn’s Disease and Their Dynamic Changes During Infliximab Therapy

Abstract: A lower biodiversity with alterations in the composition and function of faecal microbial community, characterising gut microbial dysbiosis, was observed in Chinese paediatric CD patients. IFX diminished the CD-associated gut microbial dysbiosis but was deficient in increasing certain SCFA-producing taxa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
139
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 137 publications
(154 citation statements)
references
References 53 publications
12
139
0
3
Order By: Relevance
“…Stiemsma et al (2016) reported that the abundance of genus Lachnospira (L) decreased in children with asthma, and opposing shifts in the relative abundance of Lachnospira and Clostridium neonatale (C) in the first 3 months of life were associated with preschool-age asthma, and the L/C ratio might serve as a potential early-life biomarker to predict asthma development. Wang et al (2017) found a significant loss of Lachnospira in pediatric patients with Crohn's disease prior to infliximab treatment. In the present study, the relative abundance of Ruminococcus_gnavus was higher in the CKD group.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Stiemsma et al (2016) reported that the abundance of genus Lachnospira (L) decreased in children with asthma, and opposing shifts in the relative abundance of Lachnospira and Clostridium neonatale (C) in the first 3 months of life were associated with preschool-age asthma, and the L/C ratio might serve as a potential early-life biomarker to predict asthma development. Wang et al (2017) found a significant loss of Lachnospira in pediatric patients with Crohn's disease prior to infliximab treatment. In the present study, the relative abundance of Ruminococcus_gnavus was higher in the CKD group.…”
Section: Discussionmentioning
confidence: 88%
“…Wang et al. () found a significant loss of Lachnospira in pediatric patients with Crohn's disease prior to infliximab treatment. In the present study, the relative abundance of Ruminococcus_gnavus was higher in the CKD group.…”
Section: Discussionmentioning
confidence: 99%
“…DNA was quantified using a Qubit dsDNA HS Assay Kit (Thermo Fisher Scientific, Waltham, MA, USA). PCR amplification and library preparation were accomplished using previously reported methods . In brief, amplification of the V3‐V4 hypervariable regions of the ribosomal 16S rRNA genes was performed using universal primers 341F (5′‐CCTACGGGAGGCAGCAG‐3′)/806R (5′‐GGACTACNNGGGTACTAAT‐3).…”
Section: Methodsmentioning
confidence: 99%
“…PCR amplification and library preparation were accomplished using previously reported methods. 18 In brief, amplification of the V3-V4 hypervariable regions of the ribosomal 16S rRNA genes was performed using universal primers 341F (5′-CCTACGGGAGGCAGCAG-3′)/806R (5′-GGACTACNNGGGTACTAAT-3). Purified amplicon libraries were sequenced on the MiSeq platform (Illumina, Inc, San Diego, CA) using the 2 × 300 bp paired-end protocol.…”
Section: Sample Collection Dna Isolation and 16s Rrna Gene Sequenmentioning
confidence: 99%
“…Lachnospira has been reported as depleted with respect to Crohn's disease several times 501 [35,36]. The depletion of tyzzerella has been associated with chronic intestinal 502 inflammation and supplementation suggested as a probiotic for Crohn's disease [37,38].…”
Section: Figure 3 453mentioning
confidence: 99%